Postpartum Body Condition Score (BCS) and Lactation Stage (30 and 60 Days) Affecting Essential Fatty Acids (EFA) and Milk Quality of Najdi Sheep - Abdulkareem M. Matar; Riyadh S. Aljummah (Veterinary Sciences, 2023)
Body condition scoring (BCS) can be used to assess the energy reserves of sheep during feeding, production, and weaning. The aim of this study was to evaluate the influence of BCS after parturition in stages of lactation (30 and 60 days) on the milk quality of Najdi ewes. The ewes were milked in the morning after their lambs had been isolated. Milk composition and fatty acid profiles (FA) were analyzed at 30 and 60 days of lactation after assessment of the sheep’s body condition. The sheep were classified into the following body conditions: 2.5, 3.0, 3.5, and 4.0. Sheep milk contained significant (p < 0.05) levels of protein at a BCS of 3.5 and on day 60 of lactation. The ewes with a BCS of 2.5 had a high milk content (p < 0.05) of unsaturated fatty acids (USFA), monounsaturated fatty acid (MUFA), oleic acid (OA), vaccenic acid (VA), and LA at day 60 of lactation. This result shows that the ewes with a BCS of 2.5 were able to produce high-quality milk, and 60 days of lactation was the preferred time for producing good milk and tasty and healthy dairy products.